Green Logistics and Transportation A Sustainable Supply Chain Perspective - Fahimnia, Behnam (Springer, 2015)
This chapter introduces general issues and initiates the discussion on the role of green logistics and transportation in sustainability of supply chains. General overview issues relevant to greening the supply chain, logistics network and freight/ public transportation are presented. The potential practical and research concerns that arise are the major elements of these initial issues. Given that this is the introductory chapter of the book, some reasoning and support for the need of such a book is further delineated. Introducing the chapters of the book and their interrelationships provide a broad overview of the topics covered...